O migrante na escola: um estudo de caso - Malta, May Hampshire Campos da Paz (1982)
This paper aims at describing the actual status of the migrant child who reaches his destination, more specifically, his new school contexto on the basis of the observation of pupils attending a school at Nova Iguaçu - a munipality of Rio de Janeiro State - modifications in the school curriculum are suggested, in order to offer better assistance to the migrant child as the subject of the formal educational process. The child who migrates to the Baixada Fluminense a lowland area in Rio de Janeiro State - utilizes a restricted linguistic code and becomes confronted,at school, with a different but also restricted code, utilized by non -migrant pupils, besides a third co de elaborated and used by the school as an institution. Although such codes are an obstacle hard to surmount, the migrant child manages to imitate his schoolmates within a short period of time. Both the latter and the former pupils belong to the low income section of the population. Yet, the acquisition of the code imposed by the school proves to be difficult by almost all pupils since they lack the living experiences, the attitudes and the behavior patterns prevailling in the social classes whose code the school offers. Along the adaptation process of the child to a class society, the function of the curriculum has been the stablishment of a relationship of power and control based on principles of classification and framing. In order to have a kind of education wich may promote social change, the school curriculum, in spite of not performing a primary role in such process, should be elaborated with participation of representatives of every section of the school personal and children with the purpose of preserving the several values and cultural traits. Such curriculum should be organized on the basis of the reflexion and assessment of reality.